Biosafety evaluation of Nannochloropsis oculata and Schizochytrium sp. oils as novel human milk fat substitutes. Issue 7 (10th March 2021) - Qiu, Changyang; He, Yongjin; Huang, Zicheng; Qiu, Weisang; Huang, Jian; Wang, Mingzi; Chen, Bilian
Abstract : The biosafety assessment of novel human milk fat substitutes (HMFs) from microalgae oils of Nannochloropsis oculata and Schizochytrium sp. Abstract : The biosafety assessment of novel human milk fat substitutes (HMFs) from microalgae oils of Nannochloropsis oculata and Schizochytrium sp. was evaluated by testing the cytotoxic activity using IEC-6 cells, and by conducting a sub-chronic 28-day dietary study using Sprague–Dawley (SD) suckling rats in this study. The results of the cytotoxic activity of IEC-6 cells treated with HMFs showed no apparent effect on cell viability at the tested concentrations (0–1000 μg mL −1 ). For the 28-day sub-chronic study, five rat dietary feeds with 7.5% fat were designed to have the DHA content in the range from 0 to 2.0% using corn oil as a basal oil. After the 28-day treatment, SD rats fed HMFs did not show toxicity signs and adverse effects, based on the results of clinical observation, body weight, food consumption, behavior, hematology, clinical chemistry, and necropsy findings. These results could lead to the conclusion that the inclusion of the new synthesized HMFs into the pre-weaning SD rat diet was acceptable for SD rats and did not exhibit toxic characteristics and adverse features, indicating that the HMFs from microalgal oils were safe and had the potential to be used as a promising feedstock in infant formula.